"A well-oiled machine" The limits of rentierism: The case of Saudi Arabia - Aboraya, Yasser (AUC Knowledge Fountain, 2017)
This research explores the soundness of the classical rentier state theory in analyzing oil reliant states considering oil price fluctuations and their outcomes on rentier cases. Ever since its discovery, oil has played a major role in shaping rentier economies and their policies. However, oil reliance is regarded to be a double edged sword as the huge inflows of rent could lead to a series of long-term societal and economic risks otherwise dubbed as the "rentier curse". The effects of such curse have been showing over the years in examples such as Venezuela, Saudi Arabia and several other oil reliant states. Nevertheless, not all rentier cases suffer from the same socioeconomic issues or react similarly to international oil price fluctuations. The aforementioned calls for a deeper understanding of such variations as the classic rentier state theory provides static tenets for rentierism as a "one size fits all" labeling mechanism. Although this is useful in understanding the nature of the rent seeking behavior, it is quite simplistic as some rentier states seem to suffer more than others. This has been further exacerbated by the recent and ongoing oil price drop which started in 2014 and already affected the budgets of such states. Although all oil reliant cases incurred massive deficits, some seem to be more capable of weathering the storm while other cases are preparing for drastic economic transformation. A perfect example is the Kingdom of Saudi Arabia which adopted relatively "extreme" fiscal reforms and is in the process of accomplishing the Vision 2030 plan which primarily aims at marginalizing, if not eliminating, the Saudi reliance on rent revenue. Such policies and plans, combined with the inherent fiscal, demographic and socioeconomic differences between rentier states when reacting to oil price shocks not only calls for questioning the current analytical value of the classical rentier state theory, but also calls for a post-rentier labeling for cases similar to Saudi Arabia.